Innovation and Entrepreneurship in Latin America: Recent Evidence and Challenges - Álvarez, Roberto; Grazzi, Matteo; Suárez, Diana; Vergara, Sebastian (Estudios de Economía, 2024)
In this paper, we discuss several aspects related to innovation and entrepreneurship in Latin America (LATAM). First, we document how LATAM lags behing high-income economies using various innovation indicators and how heterogeneity is a relevant issue for the region. Then, we review the main research topics related to innovation and entrepreneurship covered by economic academic research focused on the region. Within this context, we summarize the main results and contribution of the selected papers for this special issue.